A study on the influence of guardians on the oral health status of children: the reliability of gender relations domain - TC Badaria,; BS Halim,; L Naing,; NM lsmail,; AR Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Introduction: Gender relations between parents or guardians influence the health status of children including oral health. Based on their biological differences, and depending on socio-cultural contexts, parents or guardians differ in their roles, attitudes, beliefs, values and so on in bringing up children. This paper explores the importance of the gender domain in the questionnaire to study the influence of guardians on oral health status of preschool children in Pasir Mas, Kelantan. Aims: To assess the reliability of socio-culturally constructed gender relation's domain of an oral health questionnaire. Methods: A draft version of a guided questionnaire on oral health containing 120 items was developed by combining information from literature reviews, qualitative interviews on mothers and from discussions with some experts. After preliminary testing, a workshop was conducted for further adjustments before it was piloted among 100 subjects. Item analysis including internal consistenq reliability and factor analysis was used to test the reliability and construct validity of the questionnaire. Other domains were; practices, guardians' values, beliefs, attitudes and knowledge on oral health. Results: 53 items were selected based on item analysis. The internal consistency reliability of gender relation's domain was found to be 0.70 with selected 9 items, the corrected item-total correlation each item ranging from 0.1 7 to 0.61. Factor loading gave range of the items from 0.26 to 0.76 under the same component. Conclusion: The item analysis suggests that Gender domain in the fina1 version of the questionnaire was fairly good in terms of internal consistency reliability and constructs validity.